2009
DOI: 10.1179/030192309x12492910938177
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion characterisation – tool for measurement of steel cleanliness and process control: Part 2

Abstract: The research presented in this series of articles is a summary of inclusion characterisation techniques in routine to support the process improvement needs of internal customers of ArcelorMittal Global R&D, East Chicago. This paper highlights the use of characterisation techniques including total oxygen analysis, cathodoluminescence microscope on remelt buttons and clogging materials, and pulse discrimination analysis to study steelmaking and casting issues that affect productivity and quality of steel at Arce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…The inclusion amount and the measure of steel cleanliness are indicated by the total oxygen content in the steel. 6) Samples were taken from selected heats and were tested in a LECO tester to obtain total oxygen amount.…”
Section: Total Oxygen Measurementmentioning
confidence: 99%
“…The inclusion amount and the measure of steel cleanliness are indicated by the total oxygen content in the steel. 6) Samples were taken from selected heats and were tested in a LECO tester to obtain total oxygen amount.…”
Section: Total Oxygen Measurementmentioning
confidence: 99%
“…So far, only optical emission spectrometry with pulse discrimination analysis (OES-PDA) has been tested for the simultaneous analysis of steel and oxide inclusions, but the results have not been consistent with other techniques. [3] Sometimes the surface analysis can be misleading, especially when large amounts of small inclusions are present. Another challenge is the analysis of microalloying elements due to their small quantities compared to the main components.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently demonstrated that capturing cathodoluminescence (CL) images enables MgAl 2 O 4 spinel and Al 2 O 3 inclusions in steels to be distinguished more rapidly than by the conventional method . CL analysis is obtaining images and spectra based on the phenomenon of light emission from materials as a result of electron bombardment and can simultaneously identify the amount, size distribution, shape, and occasionally, composition of non‐metallic inclusions in steel …”
Section: Introductionmentioning
confidence: 99%